2012
DOI: 10.1080/09540253.2011.582033
|View full text |Cite
|
Sign up to set email alerts
|

Cultural capital and gender differences in parental involvement in children's schooling and higher education choice in China

Abstract: This article employs the concept of cultural capital to examine the ways in which social difference in terms of gender are played out in parental involvement in children's schooling and higher education choice. The intention has been to provide an in-depth analysis of the ways in which Chinese mothers and fathers are involved in the process. Semi-structured interviews were conducted with 47 secondary school students and 50 parents in Beijing. This article reveals that the transmission of cultural capital is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Therefore, gender differences in value appraisals and control could mediate differences in achieved emotional experience (Pekrun, 2006). In a study by Sheng (2012) on Chinese families, traditional cultural norms based on Confucian patriarchy were transmitted to children's educational achievement. Children's schooling was thus powerfully gendered to masculine control and female servitude.…”
Section: Test Anxiety In the Context Of Chinamentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, gender differences in value appraisals and control could mediate differences in achieved emotional experience (Pekrun, 2006). In a study by Sheng (2012) on Chinese families, traditional cultural norms based on Confucian patriarchy were transmitted to children's educational achievement. Children's schooling was thus powerfully gendered to masculine control and female servitude.…”
Section: Test Anxiety In the Context Of Chinamentioning
confidence: 97%
“…(2008) showed that cultural commandments and the distinctiveness of countries' educational settings affect differences in experiences of test anxiety across cultures. Despite China's great advancements and modernization, which are indicative of important differences between modern Chinese culture and its previous culture based on strict Confucian philosophy (Starr, 2012), Sheng (2012) has suggested that contemporary Chinese society has retained crucial Eastern psychological, social, and cultural aspects. This preservation of the traditional Chinese cultural perspective thus demonstrates that the country has in some sense retained its cultural soul while modernizing.…”
Section: Test Anxiety In the Context Of Finland And Swedenmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite distinct categories of fathers in a variety of family dynamics, prior research studies often dichotomize father types into biological fathers versus stepfathers (e.g., Sweeney, 2007;Videon, 2004), or father presence versus father absence (e. g., Vogt Yuan & Hamilton, 2006). Many studies fail to investigate fathers' influence on children's academic outcomes, instead relying on mothers' involvement to model the effect of both parents (see An & Hodge, 2013;Lai & Vadeboncoeur, 2013: Monti, Pomerantz, & Roisman, 2014von Otter, 2014;Sheng, 2012). As family demographics continue to evolve, research into the various influences of different father types becomes more important.…”
mentioning
confidence: 99%
“…Colclough, Rose and Tembon (2000) have studied the relationship between poverty, schooling and gender inequality in Guinea and Ethiopia. In China, Sheng (2012) reveals the condition of children's education in a patriarchal society, where the fathers take the role of leaders, and the mothers take a secondary role. The transmission of this cultural capital has a great effect on children's educational attainment in China.…”
Section: Literature Reviewmentioning
confidence: 99%